2014
DOI: 10.1371/journal.pone.0105333
|View full text |Cite
|
Sign up to set email alerts
|

Defence Chemistry Modulation by Light and Temperature Shifts and the Resulting Effects on Associated Epibacteria of Fucus vesiculosus

Abstract: The goals of this study were (1) to investigate whether Fucus vesiculosus regulates the production of its antifouling defence chemicals against epibacteria in response to light limitation and temperature shifts and (2) to investigate if different surface concentrations of defence compounds shape epibacterial communities. F. vesiculosus was incubated in indoor mesocosms at five different temperature conditions (5 to 25°C) and in outdoor mesocosms under six differently reduced sunlight conditions (0 to 100%), re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 34 publications
(63 reference statements)
0
50
1
Order By: Relevance
“…In the particular case of algae, proline and DMSP have been detected at the surface of the brown alga F. vesiculosus and it has been demonstrated that these compounds had antibacterial properties at natural concentrations (Saha et al ., ). More particularly, DMSP content was high at 20°C and then decreased at 25°C and was globally higher under dark conditions (Saha et al ., ). In previous works dealing with total extracts of several macroalgae, it has been demonstrated that DMSP content increased with irradiance and decreased with temperature, with such variations being in accordance with the roles of DMSP as an antioxidant or cryoprotectant (Karsten et al ., ; Lyons et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In the particular case of algae, proline and DMSP have been detected at the surface of the brown alga F. vesiculosus and it has been demonstrated that these compounds had antibacterial properties at natural concentrations (Saha et al ., ). More particularly, DMSP content was high at 20°C and then decreased at 25°C and was globally higher under dark conditions (Saha et al ., ). In previous works dealing with total extracts of several macroalgae, it has been demonstrated that DMSP content increased with irradiance and decreased with temperature, with such variations being in accordance with the roles of DMSP as an antioxidant or cryoprotectant (Karsten et al ., ; Lyons et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…qualitative control (admission of some strains and repellence of others) (Saha et al . ). Both protective (Weinberger, Hoppe & Friedlander ) and detrimental (Weinberger, Friedlander & Gunkel ; Largo, Fukami et al .…”
Section: Discussionmentioning
confidence: 97%
“…Thus, the absence of an effect of heatwaves may not be surprising, at least with respect to net defence strength. The antibacterial net defence of F. vesiculosus is a product of several active metabolites, with some of them being up‐ or down‐regulated when temperature changes (Saha et al, ). Despite maintained antibacterial defence, epibacterial abundance on the surface of adult algae was significantly reduced in 1HW.…”
Section: Discussionmentioning
confidence: 99%
“…stress tolerance, abundance of energy reserves, etc.) defence activity may be increased (Saha & Wahl, ), remain unaltered with increasing threat (Saha et al, ) or be decreased in cases of resource limitation (Sudatti, Fujii, Rodrigues, Turra, & Pereira, ). Specific components of the defence mechanism may also be impaired due to temperature stress (Weinberger et al, ).…”
Section: Introductionmentioning
confidence: 99%